Growth of single crystals of B28 at high pressures and high temperatures - Zarechnaya, Evgeniya; Dubrovinskaia, Natalia; Dubrovinsky, L.; Filinchuk, Y.; Chernyshov, D.; Dmitriev, V. (Journal of crystal growth, 2010)
A method of the high-pressure high-temperature synthesis of single crystals of orthorhombic high-pressure boron B28 from metal solutions is presented. The method is based on the high-pressure multi-anvil technique. The feasibility of single-crystal growth was demonstrated in a number of experiments conducted at various pressure-temperature conditions with various precursors including β-boron of 99.99% purity and various metals (Cu, Au, and Pt) used as fluxes and capsule materials. It was found that after dissolution in metals at high pressures and high temperatures, boron crystallizes in the form of single crystals at low temperature. The process is accompanied by chemical reactions resulting in the formation of borides. The maximum length of the B28 crystals achieved is ∼100μm.
Gesehen am 17.04.2024